Effect of magnetic field in the electrospinning of pvdf nanofibre and addition of fe3o4 - Muhammad Hamdani, Muhammad Khalil (2025)
Polyvinylidene fluoride (PVDF) is a flexible polymer with strong piezoelectric properties, making it highly suitable for applications like energy harvesting and sensors. However, obtaining the desired β-phase in PVDF, which is critical for enhanced piezoelectricity, is challenging due to its tendency to crystallize in the α-phase. This study addresses this problem by investigating the effects of an applied magnetic field using Helmholtz coils and the addition of Fe₃O₄ nanoparticles during electrospinning to promote β-phase formation. PVDF nanofibers were synthesized using the electrospinning method, with variations in the use of magnetic fields and Fe3O4nanoparticles. Structural and piezoelectric properties were analyzed using Fourier Transform Infrared Spectroscopy (FTIR) and X-Ray Diffraction (XRD). Results showed that a magnetic field enhanced β-phase formation and aligned nanofibers, improving piezoelectric properties. Similarly, Fe3O4 nanoparticles contributed to β-phase formation by facilitating crystallization. However, combining the magnetic field with Fe3O4resulted in reduced improvements due to interference effects. The study concludes that using the magnetic field and nanoparticles separately achieves the best results, providing valuable insights for optimizing PVDF nanofibers for advanced piezoelectric applications.